Comparative Analysis of Cable Stayed Bridge and Girder Bridge Considering Seismic Forces and I.R.C. Loading Using SAP2000 : A Review - Gaurav Rawat; Ravindra Kumar Raj (International Journal of Scientific Research in Civil Engineering, 2021)
A bridge is a structure which is built over some physical obstacles such as a body of water, valley, road and railway, its purpose is to provide crossing over that obstacle. Numerous bridges are in exist namely Arch Bridge, Girder Bridge, Suspension bridge, Cable stayed Bridge, etc. Design of bridges varies depending on the function of the bridge, the nature of the terrain where the bridge is constructed and anchored, the funds available to build it. Structural analysis is a process to analyze a structural system to predict its responses and behaviour by using physical laws and mathematical equations. In this study we are reviewing the literatures related to analysis of structures using analysis tool